Analisis Distribusi Logistik pada Pemilu 2019 di Kota Medan - Rika Mariska; Heri Kusmanto; Fadli Fadli (Universitas Medan Area, 2021)
This study aims to explore the 2019 election logistics distribution process carried out by the KPU of Medan City along with the obstacles that resulted in the late election logistics distribution process; finding a way out of the delay in the distribution process of election logistics in Medan City so that it is in accordance with the principles of being on time, effectively and efficiently; and to analyze the impact of late distribution of election logistics on the integrity of elections. This study used descriptive qualitative method. The results showed that many factors caused delays in the distribution of the 2019 election logistics, such as the DPTHP stage, fleet shortages, policies taken for distribution from PPS in urban villages to polling stations on April 17, 2019 before the start of voting, and others. as a way out of these problems: one, permanent distribution from KPU to PPS and finally to TPS; two, Using distribution centers (warehouses) in five constituencies in Medan City to break the concentration from one place in order to ease the work, be more focused, and minimize the occurrence of logistical delays and the exchange of ballots between electoral districts. Logistical delays indicate human error, lack of capacity and capability of election administrators.